Generalized Injectivity of Banach Modules - Fozouni, Mohammad (Sarajevo Journal of Mathematics, 2024)
In this paper, we study the notion of φ-injectivity in the special case that φ=0. For an arbitrary locally compact group G, we characterize the 0-injectivity of L^1(G) as a left L^1(G) module. Also, we show that L^1(G)^** and L^p(G) for 1<p<∞ are 0-injective Banach L^1(G) modules.